Development of Sun Tracking Solar Panel Using Arduino - Muhammad Faisal Afzan Bin Abdul Halim; Lili Azwani Binti Tiron (Journal of Engineering Technology, 2022)
As we can already observe, the global warming has a heated influence on the world. Here the impact of global warming can be taken advantage of. For operating electrical appliances, we can use solar energy as electricity. The difficulty we can observe presently is most of the solar panel used only statically by a user. The solar panel cannot charge if the solar panel is located on the east and the sun is situated on the west. So, this project is termed the "Solar Tracker". The LDR was used to feel the strength of the light at 30 degrees or a total of 180 degrees each and relayed the data to Arduino. This Arduino compares the data and rotates a servo motor toward the sun in the proper direction. The servo motor rotates the solar panel according to the highest light intensity. The solar tracker project aims to improve output power from stationary solar tracking systems. A 180-degree rotation is detected by this sun tracking device resulting the amount of energy a solar panel can generate here is far more than when it can only generate in one direction. Indirectly, the cost of acquiring more solar panels will reduced. The technology also reduces the time it takes for customers to shift the solar panel’s orientation to face the sun.